THE USE OF NUMBER HEAD TOGETHER IN TEACHING SPEAKING AT SMPN 3 POSO - Sartika Andi Patau (Program Studi PGSD Universitas Flores, 2022)
Cooperative learning with numbered head together strategy is interest because the teacher can control the group also each member of group. The objective of this study is to find out the implementation of cooperative learning with Numbered Head Together strategy in teaching speaking at Grade VII of SMPN 3 Poso. The type of the research was a qualitative research. The finding of research obtained that the implementation of Numbered head together strategy itself: first, teacher explained the material to the students. Second, teacher divided the students in to groups and gave serial number of groups. Third, students sat with the member of group and discussed and answered the task or questions. Fourth, the English teacher called one number from each group to answer or to do the task in front of the class, and the last, the other member gave support to their friends who answered or did the task. Students highest score was 93,3 and the lowest scored was 53,3. Most of the student score category was good.